Regulation of OsSAP8 Promoter in Response to Abiotic Stresses - Roszelin, Sitti ‘Aisyah Mohd; Japlus, Khairun Nisha; Goh, Hoe-Han; Md Isa, Nurulhikma (Malaysian Applied Biology, 2025)
Abiotic stresses such as drought, salinity and extreme temperatures pose significant challenges to crop production, particularly impacting rice yield and quality. These stresses are exacerbated by climate change and the escalation of the human population. Plant adaptation to abiotic stresses involves intricate molecular mechanisms, including gene expression alterations, metabolic adjustments, and stress-responsive gene activation. Phytohormones play pivotal roles in regulating these adaptive responses, by playing a central role in regulating plant growth and enhancing resilience to stress. Previous studies have shown that Oryza sativa Stress-associated protein 8 (OsSAP8) enhanced plant tolerance to drought and salinity stresses throughout the growth and developmental stages. In this study, we focused on the OsSAP8 promoter, especially the phytohormone-responsive Cis-Regulatory Elements (CREs), to deepen our understanding of its regulation under abiotic stress conditions. Promoter analysis identified several CREs associated with Abscisic Acid (ABA), Gibberellic Acid (GA) and Methyl-Jasmonate (MeJA) phytohormones. Subsequently, promoter deletion was performed using two different lengths of OsSAP8 promoter fragments, comprising different sets of phytohormone CREs. Promoter-β-glucuronidase (GUS) fusion constructs in transgenic Arabidopsis plants revealed that the truncated promoter fragment of pOsSAP8(934pb)::GUS exhibited stronger GUS activity compared to the full-length promoter, pOsSAP8(1801pb)::GUS under drought and salinity stresses. This suggests that the CREs responsible for OsSAP8 expression under stress conditions are located within this shorter promoter region. These findings underscore the importance of OsSAP8 in plant stress responses and provide a foundation for future research on enhancing agricultural sustainability amid changing environmental conditions.